Model Validation and Uncertainty Quantification, Volume 3 Proceedings of the 38th IMAC, A Conference and Exposition on Structural Dynamics 2020 - Mao, Zhu.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
Model Validation and Uncertainty Quantification, Volume 3: Proceedings of the 38th IMAC, A Conference and Exposition on Structural Dynamics, 2020, the third volume of nine from the Conference brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Model Validation and Uncertainty Quantification, including papers on: Uncertainty Quantification in Material Models Uncertainty Propagation in Structural Dynamics Practical Applications of MVUQ Advances in Model Validation & Uncertainty Quantification: Model Updating Model Validation & Uncertainty Quantification: Industrial Applications Controlling Uncertainty Uncertainty in Early Stage Design Modeling of Musical Instruments Overview of Model Validation and Uncertainty.
Keywords: Statics; Buildings -- Design and construction; Computer simulation; Engineering mathematics; Engineering -- Data processing; Mechanical Statics and Structures; Building Construction and Design; Computer Modelling; Mathematical and Computational Engineering Applications